2016
DOI: 10.1103/physrevfluids.1.074101
|View full text |Cite
|
Sign up to set email alerts
|

Superdiffusive gas recovery from nanopores

Abstract: Understanding the recovery of gas from reservoirs featuring pervasive nanopores is essential for effective shale gas extraction. Classical theories cannot accurately predict such gas recovery and many experimental observations are not well understood. Here we report molecular simulations of the recovery of gas from single nanopores, explicitly taking into account molecular gas-wall interactions. We show that, in very narrow pores, the strong gas-wall interactions are essential in determining the gas recovery b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 39 publications
2
9
0
Order By: Relevance
“…At earlier time ( t̃ < 0.01), the fluxes of both methane and ethane follow a superdiffusive scaling law Q ( t̃ ) ∼ t̃ –α with 0.4 < α < 0.5, which differs from the Q ( t̃ ) ∼ t̃ –0.5 for purely diffusive gas recovery. Similar deviation from the purely diffusive scaling law has been reported for the recovery of pure gas from nanopores, and is caused by the delayed removal of gas molecules adsorbed on the pore walls . At t̃ ≳ 0.04 ( t̃ ≳ 0.01), the production of methane and ethane from the 2 nm-wide (4 nm-wide) pore starts to deviate from the power law scaling behavior.…”
Section: Resultssupporting
confidence: 70%
See 3 more Smart Citations
“…At earlier time ( t̃ < 0.01), the fluxes of both methane and ethane follow a superdiffusive scaling law Q ( t̃ ) ∼ t̃ –α with 0.4 < α < 0.5, which differs from the Q ( t̃ ) ∼ t̃ –0.5 for purely diffusive gas recovery. Similar deviation from the purely diffusive scaling law has been reported for the recovery of pure gas from nanopores, and is caused by the delayed removal of gas molecules adsorbed on the pore walls . At t̃ ≳ 0.04 ( t̃ ≳ 0.01), the production of methane and ethane from the 2 nm-wide (4 nm-wide) pore starts to deviate from the power law scaling behavior.…”
Section: Resultssupporting
confidence: 70%
“…Molecular simulations of gas recovery are limited to systems with pores many orders of magnitude shorter than in real shale formations, and this necessarily introduces some undesirable features such as an extremely large pressure gradient along pore length and from the pore opening to the gas bath during gas recovery. Nevertheless, the fact that the present and our earlier MD simulations capture the scaling law of gas recovery rate reported in field studies and continuum simulations , suggests that these undesired features do not introduce significant artifacts into the simulation results. Therefore, MD simulations not only can be used to understand the transport and adsorption properties of gases in nanopores as demonstrated extensively in the past years, but can also be used as a powerful tool for exploring the essential physics of gas recovery process.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Besides, they also observed more adsorption for smooth surfaces than rough ones and for flexible matrix compared to a rigid one. Wu et al , observed that the gas recovery from nanopores follows a superdiffusive scaling law for single and multicomponent fluids. Furthermore, He et al studied the methane transport in clay nanopores where they doubted the applicability of the Knudsen diffusion model to estimate the methane transport under confinement.…”
Section: Atomistic Simulationmentioning
confidence: 99%